Hereditary History Preserving Simulation is Undecidable - Jurdzinski, Marcin; Nielsen, Mogens (BRICS Report Series, 1999)
We show undecidability of hereditary history preserving simulation for finite asynchronous transition systems by a reduction from the halting problem of deterministic Turing machines. To make the proof more transparent we introduce an intermediate problem of deciding the winner in domino snake games. First we reduce the halting problem of deterministic Turing machines to domino snake games. Then we show how to model a domino snake game by a hereditary history simulation game on a pair of finite asynchronous transition systems.